Urgensi Visa Haji Sebagai Syarat Sah Ibadah Haji;Analisis Pendekatan Sistem Maqasid Syariah Jaser Auda - Farhan, Muhammad; Suwandi (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
The Saudi Arabian government issued a decree that a hajj visa is a valid requirement for the hajj pilgrimage. The emergence of this decree has brought various responses, both pro from the government and several contra opinions from hajj travel service providers and influencers. This study aims to explore the philosophical basis and unravel the roots of the polemic through an analysis of the Maqashid Syariah system approach according to Jaser Auda. The method used is library research, by using Jaser Auda's book entitled “Membumikan Hukum Islam Melalui Maqashid Syariah Pendekatan Sistem, terjemah dari Maqashid Shariah as Philosophy of Islamic Law A System Approach” as the main reference. This study produced three major points, including; First, before analyzing the law, we need to understand that the legal corridor is placed between sharia (basic and absolute), fiqh (interpretative results of sharia) and fatwa (always dynamic and contextual). Second, the law on the issue of hajj visas as a valid requirement for hajj is a fatwa corridor, it is a product born from the circumstances and needs of the times. Third, the Hajj visa fatwa is not only returned to the classical maqashid which tends to prioritize individual rights, but more broadly it also prioritizes rights beyond the individual (global security concerning Human Rights).